(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
This article presents a comparative analysis of the average values of valuable economic traits such as 1000-seed weight, cotton mass per boll, fiber yield, and fiber length in the medium-fiber cotton variety “Barqaror Hosil,” developed by breeders of the Republic of Uzbekistan, in comparison with the standard varieties Namangan-77 and S-6524. The study was carried out in 2023 under the soil and climatic conditions of the Tashkent region based on scientific observations.